Ability of HIV/AIDS patients to self-diagnose oral opportunistic infections - Patton LL (Blackwell Synergy, 2001)
To assess the accuracy of HIV/AIDS patients’ self-diagnosis of common HIV-related oral opportunistic infections. Methods: 245 HIV/AIDS patients were interviewed regarding the current presence of oral candidiasis (OC), oral hairy leukoplakia (OHL), and oral ulcers prior to an oral examination by an oral medicine trained dentist examiner. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) are reported for the patient’s oral Key words: AIDS; diagnosis; hairy lesion diagnosis compared to the dentist’s diagnosis based on established pre- leukoplakia; HIV; mouth diseases; mouth mucosa; oral candidiasis; oral ulcers; sumptive clinical criteria as the gold standard.